Secondary syphilis with HIV infection in Men Who Have Sex with Men (MSM) patient treated with azithromycin and doxycycline: a case report - Hani Lusyana; Agus Walujo; Lina Damayanti (Explorer Front, 2021)
Background: Syphilis frequently presents in tandem with HIV and the prevalence is increasing, particularly in men who have sex with men (MSM). The most common and recognizable manifestations are usually the secondary stage, characterized with or without constitutional symptoms. This case study aims to evaluate secondary syphilis with HIV infection in MSM patient treated with azithromycin and doxycycline Case Presentation: A 22-year-old man with secondary syphilis and HIV infection. The diagnosis was established based on erythema and hyperpigmented maculopapular lesions with the scale on the forearms, palms, back, feet, and soles without pruritic sensation, a history of the same-sex sexual partners, and the titer of VDRL 1:64, TPHA 1:2560. The patient also has a low CD4 level and HIV-1 RNA were detected on a blood test. Patients received azithromycin 2 grams orally and continued by doxycycline twice a day for 30 days and treated for the HIV Infection. Skin disorders have improved rapidly and are significantly accompanied by decreased VDRL titer. Conclusion: The therapy of 2-gram azithromycin improved clinical manifestation on the skin. The following treatment of 30 days doxycycline showed clinical improvement and significant decline in a nontreponemal serologic test.